1998
DOI: 10.1111/j.1472-8206.1998.tb00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial β‐adrenergic reactivity in volume overload‐induced cardiac hypertrophy in the rat

Abstract: The purpose of this study was to evaluate the changes in myocardial beta-adrenergic reactivity in animals undergoing a 4 week cardiac volume overload. Aortocaval shunt (ACS) or sham operation (sham) were performed in male Wistar rats, and 4 weeks later, isoproterenol dose-effects (chronotropic, inotropic and lusitropic properties) were studied after pithing. Noradrenaline (NA) and adrenaline (A) concentrations and NA turn-over index were evaluated in plasma and heart ventricles, while beta-adrenoceptor charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…We have demonstrated a progressive increase in cardiac mass; this is in agreement with the observations of others who have employed the same needle technique for creating the aortocaval shunt (6,7,8,11,22,40,41). It should be mentioned that there are several features unique to the cardiac hypertrophic growth induced by aortocaval shunt.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We have demonstrated a progressive increase in cardiac mass; this is in agreement with the observations of others who have employed the same needle technique for creating the aortocaval shunt (6,7,8,11,22,40,41). It should be mentioned that there are several features unique to the cardiac hypertrophic growth induced by aortocaval shunt.…”
Section: Discussionsupporting
confidence: 91%
“…16,20,21,27,28). On the other hand, with the needle technique, the injury due to operation is minimized, and the shunt size can be controlled by using different sizes of needles (6,7,8,11,15,22,40,41). In this study, we have presented several novel findings, including the time course changes in myosin heavy chain isoform composition, enhanced responses to isoproterenol, increased ␤ 1 -AR density, and increased AC activity due to volume overload.…”
Section: Discussionmentioning
confidence: 87%
“…Given that Iso potentiated myocyte fractional shortening in both sham and ACF mycoytes, and pilot studies showed that Iso elicited the same increase in p-Ser23/24 cTnI (PKA phosphorylation site), the in vivo responses are not likely accounted for only by a change in β 1 -AR protein. A similar conclusion was drawn a number of years ago by Communal et al [44]. It should also be recognized that isotonic contractions of cardiomyocytes do not always adequately reflect a working heart.…”
Section: Discussionsupporting
confidence: 78%
“…Excessive activation of the sympathetic nervous system plays a major role in the development of detrimental LV remodeling and dilatation [1], and catecholamines reduce viability and protein synthesis in isolated adult cardiac myocytes [15]. However, Commual et al showed that there was no increase in the plasma concentrations of cathecholamines and a decrease in the ventricular cathecholamine level in the same AC shunt rats at 4 weeks post-surgery [7]. Wang et al demonstrated the unique characteristics of volume overloaded hearts in AC shunt rats: the β-receptor density (upregulation) and adenylyl cyclase activity increased significantly, even in the heart failure stage (16 weeks post-surgery) [21].…”
Section: Discussionmentioning
confidence: 99%